MODEL KINETIKA EKSTRAKSI FLAVONOID DARI BAYAM MERAH (Alternanthera amoena voss) - Iriany; Irsa Septiawan; Salwa Jody Gustia (Jurnal Teknik Kimia USU, 2017)
Red spinach (Alternanthera amoena voss) contains vitamins, protein, and flavonoids. Flavonoid is polyphenol compounds having properties as a free radical catcher.The purpose of this research is to obtain the kinetic rate of flavonoid mass transfer from red spinach.Extraction is one of the way to take flavonoids contained in solids with the assist of solvents. Mass transfer in liquid solid extraction occurs by diffusion. The determination of mass transfer coefficient (KC) is to conduct the rate of mass transfer of flavonoids from solids. In this study, the effect of temperature on the extraction of flavonoids from red spinach with water solvent is observed. The temperatures extraction in this research are of 50°C, 60°C, and 70°C respectively. Determinationof total flavonoid, mass transfer coefficient, and antioxidant activity carried out using FT-IR Spectrophotometry and UV-VIS Spectrophotometry. This study concluded that the increase in extraction time and temperature will increase the total content of flavonoids and extract rendement.Mass transfer coefficient equation in this study is K = 3078645 . Antioxidants in red spinach are included in the group of very strong antioxidants.